Marker-assisted introgression of multiple resistance genes confers broad spectrum resistance against bacterial leaf blight and blast diseases in Putra-1 rice variety - Chukwu, Samuel Chibuike; Yusop, Mohd Rafii; Ramlee, Shairul Izan; Ismail, Siti Izera; Abisola, Oladosu Yusuff; Kolapo, Olalekan Kazeem; Musa, Ibrahim; Halidu, Jamilu; Muhammad, Isma'ila; Adewale, Ahmed Muideen (MDPI, 2020)
Bacterial leaf blight caused by Xanthomonas oryzae pv oryzae (Xoo) and blast caused by Magnaporthe oryzae are major diseases responsible for significant yield loss in rice production across all rice growing regions. Host plant resistance has been advocated as a sustainable means of guarding against the diseases. This experiment was conducted with the aim to introgress multiple resistance genes against bacterial leaf blight and blast diseases through marker-assisted backcross breeding. Two dominant (Xa4 and Xa21) and two recessive (xa5 and xa13) Xoo resistance genes were introgressed into a high yielding Malaysian rice variety Putra-1 with genetic background of three blast resistance (Piz, Pi2 and Pi9) genes. Eight polymorphic tightly linked functional and SSR markers were used for foreground selection of target genes. Seventy nine polymorphic SSR markers were used in background selection. The plants were challenged at initial stage of breeding and challenged again at BC2F2 with the most virulent Malaysian pathotypes of Xoo (P7.7) and Magnaporthe oryzae (P7.2) to test their resistance. Results obtained from foreground marker segregation analysis at BC1F1 and BC2F1 showed that the marker polymorphism both fitted into the Mendel’s single gene segregation ratio of 1:1 for both Xoo and blast resistance. At BC2F2, results indicated that foreground marker polymorphism fitted into the expected Mendelian ratio of 1:2:1 for blast resistance only. Marker-assisted background selection revealed high percentage of recurrent parent genome recovery (95.9%). It was concluded that the inheritance of blast resistance in the introgressed lines was mainly due to single gene action while the inheritance of Xoo resistance was substantially due to single nuclear gene action. The incorporation of four bacterial leaf blight and three blast resistance genes (Xa4 + xa5 + xa13 + Xa21; Pi9 + Pi2 + Piz) in the newly developed lines would provide for broad spectrum and durable resistance against the two major diseases studied.